The Implementation of the Internship as a Coursework in Teaching and Learning Vocational Education - Amin, Nor Fadila; Abdul Latif, Adibah; Arsat, Mahyuddin; Suhairom, Nornazira; Jumaat, Nurul Farhana; Ismail, Mohd. Erfy (Journal of Technical Education and Training, 2020)
Internship is one of the common practices of higher education institutions in Malaysia for enhancing the learning experience and technical skills among their students. Students who follow the internship programme are found not only to be able to develop their professional attributes but also have the opportunity to acquire professional networks and career paths. Besides being a conventional approach that links students with real-world employment experience for a programme, internship can also be implemented for a specific course within a programme. The article discusses the implementation of an internship programme as a pedagogical approach in providing experiential learning for a specific course, i.e., Foundation and Concrete Work. This study involved 51 second-year students who were pursuing a degree in vocational education at the Universiti Teknologi Malaysia. Analysis on the impact of the internship experience indicates that the internship programme is an effective pedagogical approach for experiential learning for foundation and concrete work course.